Synthesis of Phenanthridinones from N‐Methoxybenzamides and Aryltriethoxysilanes through RhIII‐Catalyzed CH and NH Bond Activation. Issue 9 (7th June 2013) - Senthilkumar, Natarajan; Parthasarathy, Kanniyappan; Gandeepan, Parthasarathy; Cheng, Chien‐Hong
Abstract An efficient method for the one‐pot synthesis of substituted phenanthridinone derivatives from N‐methoxybenzamides and aryltriethoxysilanes through rhodium‐catalyzed dual CH bond activation and annulation reactions is described. A double‐cycle mechanism is proposed to account for this catalytic reaction. In addition, isotope‐labeling studies were performed to understand the intimate mechanism of the reaction.